Anticaries activity of GERM CLEAN in Streptococcus mutans and Candida albicans dual‐species biofilm. (21st February 2021) - Xiong, Kaixin; Chen, Xuan; Zhu, Hualing; Ji, Mengzhen; Zou, Ling
Abstract: Objective: To evaluate the antimicrobial effects of a peptide containing novel oral spray GERM CLEAN on dual‐species biofilm formed by Streptococcus mutans and Candida albicans and to investigate whether GERM CLEAN inhibits the demineralization procedure of bovine enamel in vitro. Methods: The antimicrobial effects of GERM CLEAN on dual‐species biofilm were analyzed by initial adherence rate calculation, water‐insoluble exopolysaccharides quantification, total biomass quantification, and colony‐forming units (CFUs) counting. Scanning electron microscopy and confocal laser scanning microscopy were applied to evaluate the impacts of GERM CLEAN on the biofilm structure. Further, the effects of GERM CLEAN on acidogenicity of dual‐species were appraised via glycolytic pH drop analysis and hydroxyapatite dissolution measurement. The percentage of Surface Microhardness Reduction (%SMHR) evaluation, Atomic Force Micrograph (AFM) examination, and Transverse Microradiography (TMR) analysis after pH cycling were used to determine whether GERM CLEAN inhibited the demineralization of bovine enamel. Results: GERM CLEAN decreased the adherence rate, water‐insoluble EPS production, biofilm formation, and acidogenicity of the dual‐species. Moreover, GERM CLEAN significantly inhibited the demineralization status of bovine enamels. Conclusion: This peptide containing novel oral spray GERM CLEAN has antimicrobial potential toward the dual‐species. GERM CLEAN can also impede the demineralization procedure of enamel.